ANALISIS BIBLIOMETRIK TREN DAN KEBAHARUAN STUDI PERMEABILITAS DENGAN CHEMINFORMATICS BERBASIS DATAWARRIOR - Matthew Valentino, Tambunan; Putri, Mulan Gevika Amara; Damayanti, Ni Ketut Anggun; Sianturi, Tiarma Kristiana (School of Pharmacy Institut Teknologi Bandung, 2025)
Cheminformatics is a discipline that employs computational methods on chemical data and has emerged as a cutting-edge approach in pharmaceutical sciences. DataWarrior, an open-source software that integrates big data, offers a variety of features to support cheminformatics studies. This study aims to examine permeability research using DataWarrior-based cheminformatics and evaluate the potential for research innovation, particularly within the field of pharmacy. A bibliometric analysis using the Dimensions, Biblioshiny, and ResearchRabbit databases reveals that publications on permeability studies employing DataWarrior have increased, although the number of citations has declined due to a lack of novelty in the topics. Moreover, the limited use of the keyword